Estimate for the Best Approximation of Summable Functions of Two Variables in Terms of Fourier Coefficients - Kononovych, T. O. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
An upper bound for the best approximation of periodic summable functions of two variables in the metric of L is obtained in terms of Fourier coefficients. Functions that can be represented by trigonometric series with coefficients satisfying a two-dimensional analog of the Boas–Telyakovskii conditions are considered.